Estudo documental do currículo paulista na área de química do ensino médio em perspectiva crítica de atuação docente - Jortieke Junior, João Ricardo (2022)
This research was supported by the Coordination for the Improvement of Higher Education Personnel (known as CAPES). Given recent political events and the approval, in recent years, of new curricular guidelines, it is essential to seek evidence in academic research that allows reflections on such educational policies to encourage questions and discussions for teaching activities in the classroom. With proposals, identified in a bibliographic survey, which come closer and closer to a behavioral approach to human development, the teaching role in the practical manifestation of the document becomes increasingly rigid. With the intention of providing ways of transforming these technical conditions, this research aims to analyze the proposal present in the Paulista Curriculum for High School, approved in 2020. More directly, the Support Material for Planning and Practices in Deepening (known as MAPPA, in portuguese), responsible for bringing practical guidelines to the Formative Itineraries (FI), specifically those aimed at Teaching Chemistry. Documentary Research was used as the main methodological basis and Content Analysis, with a quantitative and qualitative perspective, as a form of data analysis. Through a content analysis based on linguistics, it was possible to form thematic Registration Units (RU) focused on “suggestions” and “demands” of practices, in addition to observing the existence of vocatives in each of the RUs. Almost 60% of the RUs concern practices required by the MAPPA while conducting the FI. Talking about suggestions, the RU indicates that freedom of practice is provided only for the selection of didactic materials, experiments and other teaching resources. About the chemical knowledge, it was possible to highlight an discrepancy in the organization of the different curricular components of the FI, with some containing only four objects of knowledge and others having more than thirty.